Analisis Nilai Tambah Batagor Ikan Tenggiri (Studi Kasus di UMKM Selaras Semesta, Kota Bandung) - Binu, Marhadinda Auvira; Maulina, Ine; Suryana, Asep Agus Handaka (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Fish as a perishable food so that it can be consumed in good conditions requires efforts to maintain its freshness through the application of a cold chain (ice) system and also processing. Fish processing aims to increase the added value of fish raw materials while maintaining the quality and nutrition contained in fish so that consumers can consume the product safely and obtain its benefits. This study aims to determine how much-added value is obtained from the processing of fish batagor in the form of frozen food in which mackerel is the main raw material for fish batagor. The research was conducted at UMKM Selaras Semesta, Bandung City, West Java in March 2023 with the method used, namely the case study method with a descriptive approach. The Hayami method is used to measure and analyze the added value of processed fishery products that are studied quantitatively. The results showed that the added value generated from the batagor mackerel production activities was included in the category of high added value, which was Rp. 488,633/kg of input with a ratio of added value to product value of 78% and the amount of profit earned per kg is Rp.176,777 with a profit level percentage of 36%. The added value of mackerel batagor production is influenced by the price of raw materials, output value, and the value of other input contributions.